Impedance properties and comparison effects of different dose safranin doped hydrogels - Coskun, R.; Yalcin, O.; Okutan, M.; Ozturk, M. (ELSEVIER, 2017)
Frequency evolution of dielectric characteristics of different dose safranin (SR) doped hydrogels was studied by impedance spectroscopy (IS) at room temperature (RT). Real and imaginary parts of complex dielectric constant, impedance, electric modulus and conductivity of SR doped hydrogels were analyzed in the frequency range of 100 Hz to 40 MHz for pH 5.0 value. Phase angle, capacitance, surface resistivity, tangent factor (tan 8) for all samples were recorded with the same frequency range. Surface and bulk polarization effects wete donlinant on impedance at low and high frequency regime, respectively. Fluctuation effect of SR doped hydrogels was observed from the dielectric measurements. Tutorial of radio frequency, RF, impedance matching were realized by using the Smith chart. The coulomb interaction between SR-cations and hydrogels may be anticipated to enhance the organic electrical performance. The potential applications of SR doped hydrogels were presented to microbial fuel cells. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Hydrogels; Dielectric properties; Cole-cole plots; Ionic conductivity; Electric modulus; Impedance properties; DIELECTRIC-PROPERTIES; IONIC-CONDUCTIVITY; ELECTRICAL-CONDUCTIVITY; AQUEOUS-SOLUTIONS; AC CONDUCTIVITY; DYE; RELAXATION; LIQUID; GELS; BEHAVIOR; Materials Science